Enhancing the Morphological and Physical Characteristics of Zinc Sulphide Thin Films for Solar Cell Use during Manufacturing - Mezan, Salim Oudah (Research Highlights in Science and Technology Vol. 3, 2023)
This chapter aims to highlights the use of Photovoltaic substrates, or as a filler sheet for thin-film CIGS solar cells application. Nanotechnology is a technique that is projected to lead to dramatic improvements in many areas of the application to new materials, electronics and goods. Thin films of the zinc sulphide nanoparticle are deposited on glass substrates by thermal evaporation from ZnS NPs millimetric crystals. The alteration in the optical and structural properties of the films deposited at different (100-200 and 300)°C annealed substrates was investigated by XRD, SEM, and EDX. The findings obtained reveal that the films are structured in a cubic zinc blend with (111) preferential orientation. The visible wavelength ranges from (22 -12) nm. The strong cubic structure taken as thin layers allowed us to infer that the ZnS NPs films synthesize can be used as a buffer layer to replace the damaging CdS in CIGS thin-film solar cells. The films became more uniform and dense as the substrate temperature increased. The nanoscale size of zinc sulfide reduces as temperature rises.